PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR DAN KERJA SAMA SISWA KELAS V SD - Dewi Sekarwati; Susilo Tri Widodo; Wulan Aulia Azizah; Netri Kristiyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The subject of Pancasila education in elementary schools is considered important, but in its implementation, there are various problems, including low achievement of student learning outcomes and a lack of cooperative attitudes between them. The aim of this research is to evaluate the effectiveness of implementing the think pair share cooperative learning model in improving learning outcomes and cooperation for fifth grade elementary school students. The method used is a descriptive research method with a quantitative approach. The t-test results show that the significance value (2-tailed) is 0.00, because 0.00 < 0.05, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the use of the think pair share type cooperative learning model is effective in improving student learning outcomes. The NGain score value of 0.7916 indicates a high level of effectiveness, so it can be concluded that the use of the think pair share type cooperative learning model is classified as effective.